Effectiveness of Andaliman Extract on Blood Sugar Levels of White Mice Induced by STZ HOMA-IR - Jessyca Manishwer Kaur Dhillon; Linda Chiuman; Gusbakti Rusip (Postgraduate, University of Mataram, 2024)
The increasing cases and treatment costs have triggered the search for alternatives, such as Andaliman, which is believed to have antidiabetic and antioxidant activities, induced by Streptozotocin (STZ). Objective: to determine the effectiveness of Andaliman nanoemulsion extract in lowering blood sugar levels, overcoming insulin resistance as measured by HOMA-IR, in white mice induced by Streptozotocin (STZ). The study employed a posttest only controlled group design, using sic groups of mice, each of which had five mice weighing 150–260 grams in STZ induction (65 mg/kg), the positive control group used STZ + Metformin, the treatment group used a dose of Nanoandaliman of 25.50 & 75 mg/KgBB. KGD examination was carried out after 7.14 and 21 days after STZ induction. Results: Based on the lowest KGD measurement on day 21 in the STZ65mg/kgBB + NA50 mg/kgBB treatment group, in the HOMA-IR measurement, the highest value was found in the negative control (STZ 65mg/kgBB) on day 21. This indicates that the decrease in blood glucose levels with STZ65mg/kgBB + NA50 mg/kgBB treatment is better than other treatments on day 21. Conclusion: STZ65mg/kgBB + NA50 mg/kgBB treatment has been proven to be effective in lowering blood sugar levels. It is expected that the results of this study can become an alternative treatment for diabetes in the future